Lenvatinib suppresses cancer stem-like cells in HCC by inhibiting FGFR1–3 signaling, but not FGFR4 signaling. (25th May 2020) - Shigesawa, Taku; Maehara, Osamu; Suda, Goki; Natsuizaka, Mitsuteru; Kimura, Megumi; Shimazaki, Tomoe; Yamamoto, Koji; Yamada, Ren; Kitagataya, Takashi; Nakamura, Akihisa; Suzuki, Kazuharu; Ohara, Masatsugu; et al.
Abstract: In hepatocellular carcinoma (HCC), a subset of cells defined by high CD44 and CD133 expression has been reported to possess cancer stem-like cell (CSC) characteristics and to be associated with a poor prognosis. Since the approval of the multikinase inhibitor, lenvatinib, for patients with unresectable HCC, two such inhibitors (sorafenib and lenvatinib) have been employed as first-line systemic chemotherapeutics for these patients. Based on differences in the kinase-affinity profiles between these two drugs, evidence has suggested that both exert different effects on HCC, although these differences are not fully characterized. In this study, using in vitro and a preclinical in vivo xenograft mouse model, we showed that lenvatinib alone (not sorafenib or the cytotoxic agent, 5-fluorouracil) diminished CD44 High /CD133 High CSCs in HCC. Furthermore, western blotting and reverse transcriptase-polymerase chain reaction analysis revealed that the expression of fibroblast growth factor receptor (FGFR)-1–4 differed between CD44 High /CD133 High CSCs and control cells. Analysis of the effects of selective FGFR inhibitors and FGFR small interfering RNAs on CSCs in HCC revealed that lenvatinib diminished CSCs in HCC by inhibiting FGFR1–3 signaling, however, FGFR4 signaling was not impacted. Finally, we showed that FGF2 and FGF19 were involved in maintaining CD44 High /CD133 High CSCs in HCC, potentially, via FGFR1–3. The findings provide novel mechanistic insights into the effects of lenvatinib on CSCs in HCC and provide clues for developing effective targeted therapies against CSCs in HCC. Abstract : Lenvatinib, not sorafenib, exerted potent anti-CSC activity in HCC by suppressing FGFR signaling. Furthermore, FGFR1–3-mediated signaling, not FGFR4-mediated signaling, was pivotal in regulating CSC maintenance.